Решите дробное рациональное выражение

iskandarova174 iskandarova174    1   23.11.2019 22:53    0

Ответы
kotenok88 kotenok88  11.09.2020 13:59

х=1

Объяснение:

\frac{2}{x-3} +\frac{1}{x+2} =\frac{x^{2}+4x-1}{x^{2}-x-6} \\\frac{2(x+2)}{(x-3)(x+2)} +\frac{1(x-3)}{(x+2)(x-3)} -\frac{x^{2}+4x-1}{x^{2}-x-6} =0\\\frac{2x+4+x-3}{x^{2}-3x+2x-6} -\frac{x^{2}+4x-1}{x^{2}-x-6} =0\\\frac{3x+1}{x^{2}-x-6} -\frac{x^{2}+4x-1}{x^{2}-x-6} =0\\\frac{3x+1-x^{2}-4x+1}{x^{2}-x-6} =0\\\frac{-x^{2}-x+2}{x^{2}-x-6} =0\\\left \{ {-x^{2}-x+2=0} \atop {x^{2}-x-60}} \right. \\1)-x^{2}-x+2=0\\D=1+8=9

x=(1±3)/-2

x=1, x=-2

2)x²-x-6≠0

D=1+24=25

x≠(1±5)/2

x≠3, x≠-2

Подставим в систему

\left \{ {{x=1, x=-2} \atop {x-2, x3}} \right.⇒x=1

ответ: х=1

Примечание: Знак неравенства ≠ в системах соответствует <>

ПОКАЗАТЬ ОТВЕТЫ